1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Find an equation in standard form for the conic. Calculus II

  1. May 7, 2012 #1
    1. The problem statement, all variables and given/known data

    Find an equation in standard form for the conic ,
    a)Ellipse: vertices (0,0) & (0,8), foci (0,2) & (0,6).
    b) hyperbola: vertices (-3,0) & (3,0), asymptotes y= ±2x

    2. Relevant equations
    Ellipse: (x-h)^2/b^2+(y-k)^2/a^2=1, vertices ± a from center, foci ± c from center, c^2=a^2-b^2, a<b, ceneter = (h,k)
    Hyperbola: (x-h)^2/a^2-(y-k)^2/b^2=1, vertices ± a from center, foci ± c from center, c^2=a^2+b^2, ceneter = (h,k), asymptotes= k±b/a(x-h)

    3. The attempt at a solution

    a) foci are ±c from center, the foci are (0,2) & (0,6) thus h must = 0, c must= 2, c^2=4, and k= 4
    I know c, and the center (0,4)
    vertices are ± a from the center thus if the center is (0,4) when vertices are ( 0,0) & (0,8), a must= 4 and a^2=16
    since I know have a^2 and c^2 I can solve for b^2
    4=16-b^2, b^2=12
    I can now solve the problem and write the equation in the form of (x-h)^2/b^2+(y-k)^2/a^2=1.
    End part A

    vertices are ± a from center @ (±3,0) thus the center is (0,0) h=0, k=0 and a=3 and a^2=9
    asymptotes are in the form of k±b/a(x-h) thus 0 ± b/3(x-0)= ±2x, b must =6 b^2=36
    I can now write the equation in the form of (x-h)^2/a^2-(y-k)^2/b^2=1 as:

    End part B

    That is all my work/solutions for this problem.
    Any help with what I may have done wrong and how to learn how to correct is, or even just saying "correct" is appreciated thank you.
  2. jcsd
  3. May 7, 2012 #2


    User Avatar
    Science Advisor

    Assuming an ellipse is set up with foci on the x-axis, we can take them to be at (c, 0) and (-c, 0). We can take the vertices on the major axis to be at (a, 0) and (-a, 0). The distance from the focus (-c, 0) to (a, 0) is a-(-c)= a+ c and the distance from that vertex to the other focus, (c, 0) is a- c. That is, the total distance from focus to vertex to other vertex, along the major axis, is a+ c+ a- c= 2a.

    The distance from the focus (c, 0) to the vertex on the minor axis, (0, b) is [itex]\sqrt{b^2+ c^2}[/itex]. The distance from (0, b) to (-c, 0) is also [itex]\sqrt{b^2+ c^2}[/itex] so the distance form focus to vertex to the other vertex, on the minor axis is [itex]2\sqrt{b^2+ c^2}[/itex].

    Now, a defining property of an ellipse is that the distance from one focus, to any point on the ellipse, back to the other vertex is a constant. Therefore, we must have [itex]2\sqrt{b^2+ c^2}= 2a[/itex] so, dividing both sides by 2 and squaring both sides, [itex]b^2+ c^2= a^2[/itex]. I would be surprised if you were not given that formula in you class or textbook.

    You are given a and c so you can use that to find b.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook